Implementasi Strategi Multidimensional Dalam Pemberdayaan Siswa SD Negeri 1 Megu Gede Cirebon Melalui Program Kuliah Pengabdian Masyarakat - Muhammad Iqbal AL Ghozali; Saehu Abas; Firmansyah; Athoillah Islamy (Pusmedia Group Indonesia, 2026)
The rapid development of digital technology and the increasing demand for twenty-first-century skills require elementary schools not only to enhance students’ digital literacy but also to foster character development, creativity, and healthy living awareness. However, these aspects remain significant challenges in empowering elementary school students holistically. This Community Service Program aimed to implement a multidimensional strategy for empowering students at SD Negeri 1 Megu Gede, Weru District, Cirebon Regency, through strengthening digital literacy, environment-based creativity, bullying prevention, and health education. The program employed educational and participatory outreach and socialization methods supported by audiovisual media, demonstrations, hands-on practice, and mentoring activities. The program was conducted over four days and involved students from grades two to six. The implemented activities included digital literacy training using Google Sheets, Wordwall, and Canva, an ecoprint workshop utilizing natural materials, anti-bullying socialization sessions, and handwashing education accompanied by practical demonstrations. The results indicated increased student participation and understanding of digital technology utilization, greater awareness of anti-bullying behavior, improved healthy and clean living practices, and enhanced creativity and environmental awareness through ecoprint activities. Therefore, the implementation of a multidimensional strategy through the Community Service Program contributed to the comprehensive empowerment of elementary school students by strengthening digital literacy, character development, health awareness, and creativity as essential competencies for addressing twenty-first-century challenges.